MicroRNA-155 Promotes Heat Stress-Induced Inflammation via Targeting Liver X Receptor α in Microglia - Li, Ping; Wang, Gong; Zhang, Xiao-Liang; He, Gen-Lin; Luo, Xue; Yang, Ju; Luo, Zhen; Shen, Ting-Ting; Yang, Xue-Sen (Frontiers in Cellular Neuroscience, 2019)
Background：The neuroinflammatory responses of microglial cells play an important role in the process of brain dysfunction caused by heat stroke. MicroRNAs are reportedly involved in a complex signalling network and have been identified as neuroinflammatory regulators. In this study, we determined the biological roles of microRNA-155 in the inflammatory responses in heat-stressed microglia and explored the underlying mechanisms. Methods： MicroRNA-155 mimic and inhibitor were used to separately upregulate or downregulate microRNA-155 expression. The activation state of BV-2 microglial cells (BV-2 cells) was assessed via immunoreactions using the microglial marker CD11b and CD68. Levels of induced interleukin-1β (IL-1β), interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) were measured using real-time reverse transcription polymerase chain reaction (RT-PCR) and enzyme linked immunosorbent assays (ELISAs). The activation of nuclear factor kappa B (NF-κB) signalling proteins was evaluated by Western blotting for inhibitory kappa B alpha (IκBα) and NF-κB p65 phosphorylation and indirect immunofluorescence analysis using a p65 phosphorylation antibody. A luciferase reporter assay was used to verify liver X receptor α (LXRα) as a target gene of microRNA-155. Results： Heat stress significantly induced IL-1β, IL-6 and TNF-α release and increased the expression of CD11b and CD68. In addition, IκBα and NF-κB p65 phosphorylation were dramatically increased by heat stress, and microRNA-155 expression was also elevated. High expression of microRNA-155 in heat-stressed microglial cells was inversely correlated with LXRα expression. We then determined the role of microRNA-155 in the heat stress-induced inflammatory responses. The results revealed that by targeting LXRα, microRNA-155 enhanced NF-κB signalling activation and facilitated immune inflammation in heat stress-treated BV-2 cells. Conclusions：MicroRNA-155 promotes heat stress-induced inflammatory responses in microglia. The underlying mechanisms may include facilitating inflammatory factors expression by increasing NF-κB pathway activation via targeting LXRα.